Small bowel metastasis during organ preservation in patients with esophageal squamous cell carcinoma: case report and literature review - Cao, Qinxing; Lu, Hejiang; Niu, Liangbo; Zhao, Xiaofang; Yan, Li; Liu, Yisha; Pang, Minghui (Frontiers in Oncology, 2025)
BackgroundFor patients with locally advanced esophageal squamous cell carcinoma (ESCC) who achieve a clinical complete response (cCR) after comprehensive treatment, organ preservation and observation-waiting strategies provide a more conservative treatment option that enhances the patient’s quality of life. The high cCR rate of chemoradiotherapy combined with immunotherapy is driving the shift in ESCC treatment from traditional radical surgery to organ preservation.Case summaryWe report a case of a 57-year-old male patient diagnosed with esophageal ESCC who underwent combined radiotherapy, chemotherapy, and immunotherapy. After treatment, the patient achieved a cCR, resulting in 15 months of progression-free survival. At this stage, the primary lesion showed no signs of local regrowth or recurrence; however, unexpected metastasis to the small intestine occurred, leading to bowel obstruction. The metastasis at this occult site was not detected by sensitive monitoring methods, and the side effects of the immunotherapy drugs further complicated the diagnosis and differential diagnosis. The tumor metastasis at the unexpected site was not identified early, but following rescue surgery, the patient survived for an additional 6 months.ConclusionsOrgan-preserving surgery for esophageal cancer significantly improves patients’ short-term quality of life. However, owing to incomplete monitoring measures, a cautious approach should be maintained when implementing organ-preserving surgery at this stage. For patients undergoing organ-preserving surgery, continuous active monitoring is essential. Timely intervention should be provided when clinical symptoms arise, and personalized treatment plans should be developed, while remaining vigilant for metastasis at unexpected sites.